Polyglycolic acid copolymers and methods for their preparation

CN119143976BActive Publication Date: 2026-10-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310704027.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2026-10-13
Estimated Expiration
2043-06-14

AI Technical Summary

Technical Problem

开环共聚的优点是催化剂用量少、产品热性能优异、共聚物分子量高,但也存在原料成本高、种类少的缺点,极大限制了它的应用

Benefits of technology

[0015](1)本发明制备方法包括酯化反应、预聚与缩聚过程,特定的催化剂体系与特定的工艺流程协同作用,能够解决聚乙醇酸制备过程中容易氧化和降解,加工困难的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the polyglycolic acid reaction field and discloses a polyglycolic acid copolymer and a preparation method thereof, which comprises the following steps: under the action of a first catalyst and a second catalyst, a first monomer, a second monomer and a third monomer are subjected to esterification to obtain a precursor; the precursor is subjected to prepolymerization under the condition of a second temperature and a first pressure to obtain an intermediate; the intermediate is subjected to polycondensation under reduced pressure to obtain the copolymer; the first monomer is glycolic acid and / or glycolate; the second monomer is selected from binary acid and / or binary anhydride; the third monomer is selected from binary alcohol; and the second catalyst is a catalyst of the RE(R1)3 type. The method has low cost, is easy to process, and the polymer is stable during the processing process and is not prone to oxidation and degradation; the prepared polyglycolic acid copolymer has high thermal stability, high viscosity and excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyglycolic acid, and more specifically, to a polyglycolic acid copolymer and a method for preparing the same. Background Technology

[0002] With the development of the economy and society, the environmental protection requirements for polymer materials are getting higher and higher. Developing biodegradable polymer materials is an effective way to solve the problem of "white pollution".

[0003] Currently, biodegradable polymer materials also have certain limitations. For example, the simplest linear aliphatic polyester polyglycolic acid (PGA), although it has high strength, modulus and gas barrier properties, has a melting point (220-225℃) close to its thermal decomposition temperature (around 250℃), poor thermal stability, difficulty in synthesis and processing, narrow processing window, serious degradation of product performance during processing, and excessively high rigidity (elongation at break is generally between 30-40%), making it unsuitable for direct use as a membrane material. It is also insoluble in common organic solvents, which greatly limits its processing methods and applications. Furthermore, the thermal stability of the raw material glycolic acid is insufficient, and it is extremely prone to thermal oxidative degradation under polycondensation reaction conditions.

[0004] Currently, the main copolymerization method for PGA is ring-opening polymerization, with monomers such as lactide, ε-caprolactone, and trimethylene carbonate being the primary copolymers. The advantages of ring-opening copolymerization include low catalyst usage, excellent thermal properties of the product, and high molecular weight copolymers. However, it also has disadvantages such as high raw material costs and a limited variety of raw materials, which greatly restricts its application. In contrast, high molecular weight copolymers obtained through the polycondensation of glycolic acid or ethanol esters with other polyester monomers can significantly reduce raw material costs and eliminate the need for lengthy solid-state polycondensation, thus facilitating large-scale production. Summary of the Invention

[0005] The purpose of this invention is to overcome the problems of polyglycolic acid having a melting point close to its thermal decomposition temperature, being easily oxidized and degraded during preparation, and having a narrow processing window in the existing technology. This invention provides a polyglycolic acid copolymer and its preparation method. This method is less expensive than ring-opening polymerization. The synergistic effect of a suitable catalyst system and pressure system makes the product stable in performance during processing, less prone to oxidation and degradation, easy to process, and can obtain polyglycolic acid copolymers with high thermal stability, high viscosity, and excellent mechanical properties.

[0006] To achieve the above objectives, the first aspect of the present invention provides a method for preparing a polyglycolic acid copolymer, comprising the following steps:

[0007] (1) At a first temperature, the first monomer, the second monomer and the third monomer are subjected to an esterification reaction under the action of the first catalyst and the second catalyst to obtain the precursor;

[0008] (2) The precursor is prepolymerized at a second temperature and a first pressure to obtain an intermediate; the intermediate is polycondensed at a second pressure to obtain a copolymer.

[0009] The first monomer is glycolic acid and / or glycolate;

[0010] The second monomer is selected from diacids and / or diacid anhydrides;

[0011] The third monomer is selected from diols;

[0012] The second catalyst is a RE(R1)3 type catalyst, where RE is a rare earth metal element, R1 is selected from at least one of halogen, alkoxy, aryloxy, acetylacetonate, and R2COO- groups, and R2 is C1-C 30 Alkyl groups.

[0013] A second aspect of the present invention provides a polyglycolic acid copolymer prepared by the aforementioned method.

[0014] Through the above technical solution, the present invention has the following beneficial effects:

[0015] (1) The preparation method of the present invention includes esterification reaction, prepolymerization and polycondensation process. The specific catalyst system and specific process flow work together to solve the problems of easy oxidation and degradation and difficult processing of polyglycolic acid during preparation.

[0016] (2) The polyglycolic acid copolymer prepared by the specific method of the present invention has excellent mechanical properties such as high thermal stability, high viscosity and high toughness. Detailed Implementation

[0017] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0018] The first aspect of this invention provides a method for preparing a polyglycolic acid copolymer, comprising the following steps:

[0019] (1) At a first temperature, the first monomer, the second monomer and the third monomer are subjected to an esterification reaction under the action of the first catalyst and the second catalyst to obtain the precursor;

[0020] (2) The precursor is heated to a second temperature and a first pressure to undergo a prepolymerization reaction to obtain an intermediate; the intermediate is then depressurized to a second pressure to undergo a polycondensation reaction to obtain a copolymer.

[0021] The first monomer is glycolic acid and / or glycolate;

[0022] The second monomer is selected from diacids and / or diacid anhydrides;

[0023] The third monomer is selected from diols;

[0024] The second catalyst is a RE(R1)3 type catalyst, where RE is a rare earth metal element, R1 is selected from at least one of halogen, alkoxy, aryloxy, acetylacetonate, and R2COO- groups, and R2 is C1-C 30 Alkyl groups.

[0025] In this invention, a specific preparation method enables polyglycolic acid to have high thermal stability during preparation, making it less prone to oxidation and degradation. Specifically, the addition of a specific second catalyst during the preparation process affects the polymerization process, increasing the polymer viscosity, resulting in a higher degree of polymerization and improved mechanical properties. The preparation process involves raising the temperature from a first temperature to a second temperature and lowering the pressure from a first pressure to a second pressure. By adjusting the reaction temperature and pressure, the normal progress of the reaction is ensured, resulting in a longer processing window compared to existing technologies.

[0026] According to the present invention, the rare earth metal element is selected from at least one of yttrium, lanthanum, cerium, praseodymium, neodymium, terbium, ytterbium, dysprosium, samarium and scandium, preferably at least one of lanthanum, cerium and neodymium.

[0027] According to the present invention, the halogen is selected from at least one of fluorine, chlorine and bromine, preferably chlorine.

[0028] According to the present invention, the alkoxy group is selected from C3-C6 alkoxy groups, preferably C6 alkoxy groups.

[0029] According to the present invention, the aryloxy group is selected from aryloxy groups containing at least one benzene ring or naphthalene ring, preferably phenoxy groups.

[0030] According to the present invention, R1 is selected from acetylacetone.

[0031] In this invention, the inventors unexpectedly discovered during the experiment that when R1 is selected as an acetylacetone group, it can effectively form a coordination structure with rare earth elements, resulting in higher catalyst activity and thus generating a high-viscosity polymer sample.

[0032] According to the present invention, R2 is selected from C1-C20 alkyl groups.

[0033] According to the present invention, the second catalyst is lanthanum acetylacetonate.

[0034] According to the present invention, the molar ratio of the first monomer to the second monomer is 0.1-9:1, preferably 0.2-4:1, and more preferably 0.8-2:1.

[0035] In this invention, a specific ratio of the first monomer, the second monomer, and the third monomer can improve the toughness of the copolymer while maintaining the excellent crystallinity, strength, and other mechanical properties of polyglycolic acid itself.

[0036] According to the present invention, the molar ratio of the third monomer to the second monomer is 1.1-2:1; preferably 1.15-1.5:1, more preferably 1.2-1.3:1.

[0037] According to the present invention, the molar ratio of the first catalyst to the total molar ratio of the first monomer and the second monomer is 1:(3.33×10⁻⁶). 2 )-10 5 .

[0038] According to the present invention, the molar ratio of the second catalyst to the total molar ratio of the first monomer and the second monomer is 1:(3.33×10⁻⁶). 2 )-10 5 .

[0039] In this invention, the specific type of catalyst and the ratio of the molar amount of the specific first catalyst to the total molar amount of the first monomer and the second monomer, and the ratio of the molar amount of the specific second catalyst to the total molar amount of the first monomer and the second monomer, have a synergistic effect, which can significantly increase the polymer viscosity, thereby increasing the polymer molecular weight and degree of polymerization, reducing the polymer end group content, which is beneficial to increasing the polymer decomposition temperature. At the same time, the increase in polymer molecular weight is also beneficial to the improvement of polymerization mechanical properties.

[0040] According to the present invention, the molar ratio of the first catalyst to the total molar ratio of the first monomer and the second monomer is 1:(5×10⁻⁶). 2 )-(2×10 4 ), more preferably 1: (2×10 3 )-10 4 .

[0041] According to the present invention, the molar ratio of the second catalyst to the total molar ratio of the first monomer and the second monomer is 1:(2×10⁻⁶). 3 )-10 5 More preferably, it is 1:(2×10 4 )-10 5 .

[0042] According to the present invention, the first catalyst is selected from at least one of phosphoric acid, sulfuric acid, organic sulfonic acid, inorganic metal salt, metal oxide and organometallic salt.

[0043] According to the present invention, the metal element in the inorganic metal salt, the metal oxide, and the organometal salt is selected from at least one metal element in groups IIB, IIIB, IVB, VB, VIII, IIIA, IV, and VA of the periodic table.

[0044] According to the present invention, the metal element in the inorganic metal salt, the metal oxide, and the organometal salt is selected from at least one of the group IIB, IIIB, IVB, VB, VIII, IIIA, IV, and VA metal elements in the third, fourth, and fifth periods of the periodic table.

[0045] According to the present invention, the metal element in the inorganic metal salt, the metal oxide, and the organometal salt is selected from at least one of zinc, titanium, vanadium, tin, antimony, and bismuth.

[0046] According to the present invention, the metal element in the inorganic metal salt, the metal oxide and the organometal salt is selected from tin and / or antimony.

[0047] According to the present invention, the metal element in the inorganic metal salt, the metal oxide, and the organometal salt is tin.

[0048] According to the present invention, the metal-bonded portion of the organometal salt is selected from C1-C20 oxygenated alkanes.

[0049] According to the present invention, the metal-binding portion of the organometal salt is selected from at least one of α-alkoxy, α-alkyl monocarboxylic acid, α-alkyl monocarboxylic acid, α,ω-alkyl diacid, alkyl monoketone and polyketone.

[0050] According to the present invention, the first catalyst is selected from at least one of zinc acetate, tetraisopropyl titanate, tetrabutyl titanate, diacetylacetonate diisopropyl titanate, acetylacetonate titanium oxyacetate, vanadium oxalate, cobalt oxalate, dibutyltin oxide, diacetylacetonate dibutyltin, dibutyltin diacetate, tin laurate, methylphenyltin oxide, tetraethyltin, hexaethyltin oxide, hexacyclohexylditin oxide, di(dodecyl)tin oxide, triethylhydroxytin, triphenylhydroxytin, triisobutyltin acetate, diphenyltin dilaurate, monobutyltin trichloride, tributyltin chloride, dibutyltin sulfide, butyl hydroxytin oxide, methylstannic acid, ethylstannic acid, butylstannic acid, stannous octoate, stannous acetate, stannous oxalate, antimony trioxide, bismuth neododecanoate, bismuth acetate, and bismuth oxalate.

[0051] According to the present invention, the first catalyst is selected from at least one of dibutyltin oxide, dibutyltin diacetylacetone, dibutyltin diacetate, stannous octoate, stannous acetate, stannous oxalate, and antimony trioxide.

[0052] According to the present invention, the first catalyst is selected from at least one of stannous octoate, stannous acetate, and stannous oxalate.

[0053] According to the present invention, the first catalyst is stannous oxalate.

[0054] According to the present invention, the dicarboxylic acid is selected from at least one of 2,5-furandicarboxylic acid, terephthalic acid, phthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 1,4-succinic acid, 1,5-glutaric acid, 1,6-adipic acid, 1,8-octanoic acid, 1,10-sebacic acid, and 1,4-cyclohexanedicarboxylic acid.

[0055] According to the present invention, the dicarboxylic acid is selected from at least one of 2,5-furandicarboxylic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, 1,4-succinic acid, 1,6-adipic acid, 1,10-sebacic acid and 1,4-cyclohexanedicarboxylic acid.

[0056] According to the present invention, the dicarboxylic acid is selected from at least one of 2,5-furandicarboxylic acid, terephthalic acid, and 1,10-sebacic acid.

[0057] According to the present invention, the dicarboxylic acid is terephthalic acid and / or 1,10-sebacic acid.

[0058] According to the present invention, the dicarboxylic anhydride is selected from malondiic anhydride, succinic anhydride, glutaric anhydride, adipic anhydride, sebacic anhydride and phthalic anhydride, preferably sebacic anhydride.

[0059] According to the present invention, the diol is selected from at least one of ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,2-propanediol, 2-methyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, 1,3-butanediol, neopentanediol, 1,4-cyclohexanediol, 1,6-cyclohexanediol, diethylene glycol, triethylene glycol, polyethylene glycol, p-phenol, diethyl terephthalate, dihydroxypropyl terephthalate, dihydroxybutyl terephthalate, dihydroxyhexyl terephthalate, tetrahydrofuran 3,4-diol, isosorbide, iso-idyl alcohol, and isomannitol.

[0060] According to the present invention, the diol is selected from at least one of ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,2-propanediol, 2-methyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, diethyl terephthalate, dipropyl terephthalate, dibutyl terephthalate, dihexyl terephthalate, tetrahydrofuran 3,4-diol, and isosorbide.

[0061] According to the present invention, the diol is selected from at least one of ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, diethyl terephthalate, dibutyl terephthalate, dihexyl terephthalate, and isosorbide.

[0062] According to the present invention, the diol is 1,4-butanediol and / or bis(hydroxybutyl) terephthalate.

[0063] According to the present invention, step (1) further includes: performing a deoxygenation operation before the reaction to ensure that both the first esterification reaction and the second esterification reaction are carried out in an inert gas atmosphere.

[0064] In this invention, an oxygen removal process is performed in advance to further prevent oxidation during the preparation of polyglycolic acid.

[0065] According to the present invention, the deoxygenation time is 10-100 min, preferably 10-30 min.

[0066] According to the present invention, the first temperature is 100-190°C.

[0067] In this invention, a specific first temperature ensures the smooth progress of the esterification reaction. The temperature of the esterification reaction cannot be too high or too low. When the temperature of the esterification reaction is below 100°C, the esterification reaction rate is too low, which is not conducive to subsequent reactions. When the temperature of the esterification reaction is above 190°C, the raw materials are prone to sublimation and decomposition, resulting in an excessively high raw material loss rate.

[0068] According to the present invention, the first temperature is 175-185°C.

[0069] According to the present invention, the esterification reaction takes 1-6 hours.

[0070] In this invention, the esterification reaction time cannot be too long or too short. When the esterification reaction time is less than 1 hour, the raw material reaction is insufficient, the esterification rate is too low, and the raw material loss rate is too high. When the esterification reaction time is greater than 6 hours, it will cause energy waste.

[0071] According to the present invention, the esterification reaction takes 2-4 hours.

[0072] According to the present invention, the second temperature is 190-235°C, preferably 200-225°C.

[0073] According to the present invention, the first pressure is 0.1-100 kPa; preferably 0.1-2 kPa.

[0074] According to the present invention, the prepolymerization reaction time is 0.5-2 hours, preferably 1-2 hours.

[0075] In this invention, a pre-condensation reaction is first carried out under low vacuum to extract excess diol, preventing the excess diol from causing the polymer molecular weight to be too low.

[0076] According to the present invention, the second pressure is ≤200Pa, preferably 20-200Pa.

[0077] According to the present invention, the temperature of the polycondensation reaction is 190-235°C, preferably 200-225°C.

[0078] According to the present invention, the polycondensation reaction takes 1-6 hours, preferably 2-4 hours.

[0079] In this invention, under the conditions of high vacuum and specific polycondensation process, when the final polycondensation reaction is carried out until the polymerization reaction is completed, there will be a significant increase in system viscosity, namely the Weissenberg effect.

[0080] A second aspect of the present invention provides a polyglycolic acid copolymer prepared by the aforementioned method.

[0081] According to the present invention, the thermal decomposition temperature of the polyglycolic acid copolymer is ≥300℃, and the intrinsic viscosity at 25℃ is ≥1dL / g.

[0082] In this invention, the polyglycolic acid copolymer prepared by a specific method exhibits excellent thermal stability and intrinsic viscosity.

[0083] According to the present invention, the thermal decomposition temperature of the polyglycolic acid copolymer is 322°C, and the intrinsic viscosity is 1.2 dL / g.

[0084] The present invention will be described in detail below through embodiments.

[0085] In the following embodiments, the glass transition temperature (T) g ), melting point (T) m ), crystallization temperature (T) cThe parameters were measured using a Q100 differential scanning calorimeter from TA Instruments (USA). This instrument is equipped with a mechanical cooling system for precise control of the heating and cooling process. The instrument temperature was calibrated using n-octane (melting point -56.76℃) and indium (melting point 156.78℃). The instrument temperature control is accurate to ±0.01℃, and the detection temperature range is -80℃ to 400℃. Sample volumes ranged from 2-5 mg, and all samples were tested under a nitrogen atmosphere at a flow rate of 50 mL / min and a heating / cooling rate of 10℃ / min.

[0086] Decomposition temperature (T) d The decomposition temperature was determined using a TA Instruments Q500 SDT thermogravimetric-differential thermal analyzer, with the temperature at which 5 wt% weight loss was defined as the decomposition temperature. The test was conducted under a nitrogen atmosphere at a flow rate of 100 mL / min, a temperature scan range of 40-600 °C, and a heating rate of 10 °C / min. Sample amounts of 2-10 mg were placed in platinum crucibles for the test.

[0087] The intrinsic viscosity test method is as follows: Accurately weigh 0.1±0.5g of ground polyester sample, dissolve it in a chloroform solution containing 5nM, and test the outflow times t0 and t of the pure solvent and polymer solution respectively in a constant temperature water bath at 25±0.5℃ using a 0.5-0.6mm diameter Ubbelohde viscometer. The intrinsic viscosity [η] is calculated using the "one-point method" formula [Thomes DK, Thomes TA.J.Appl.Polym.Sci,1960,3:129-131].

[0088] [η]=[2(η sp -lnη r )] 1 / 2 / c

[0089] Where: η r =t / t0 is the relative viscosity; η sp =η r -1 represents the specific viscosity, and c represents the polymer solution concentration.

[0090] The mechanical property testing method was as follows: An Instron 5965 universal electronic tensile testing machine (USA) was used to test the uniaxial tensile properties of the specimens according to GB / T1040.2-2006 standard. The tensile rate was 50 mm / min, and the test was conducted at room temperature. The samples were hot-pressed dumbbell-shaped strips, and each sample underwent five parallel tests, with the average value taken.

[0091] Unless otherwise specified, all experimental materials used in the following examples are commercially available.

[0092] Example 1

[0093] 1.6 mol glycolic acid, 0.8 mol sebacic acid, 1.04 mol ethylene glycol, 0.25 mmol stannous oxalate catalyst, and 0.025 mmol lanthanum acetylacetone were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification for 3 h. The reaction temperature was then controlled at 215 °C and the reaction pressure at 2 kPa for prepolymerization for 1 h. When excess ethylene glycol was extracted and the system temperature did not rise, it was confirmed that the ethylene glycol had been extracted. The reaction temperature was then controlled at 215 °C and the reaction pressure at 20 Pa for polycondensation for 3 h. The product discharged was polyglycolic acid copolyethylene sebacic acid ester A1.

[0094] Example 2

[0095] 1.6 mol glycolic acid, 0.8 mol terephthalic acid, 1.04 mol butanediol, 0.6 mmol stannous oxalate catalyst, and 0.06 mmol lanthanum acetylacetone were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification for 3 h. The reaction temperature was then controlled at 215 °C and the reaction pressure at 2 kPa for prepolymerization for 1 h. When excess butanediol was extracted and the system temperature did not rise, it was confirmed that butanediol had been extracted. The reaction temperature was then controlled at 215 °C and the reaction pressure at 20 Pa for polycondensation for 3 h. The product discharged was poly(glycolic acid) copolymer butylene terephthalate A2.

[0096] Example 3

[0097] 1.6 mol glycolic acid, 1 mol sebacic acid, 1.3 mol ethylene glycol, 0.3 mmol tetrabutyl titanate catalyst, and 0.03 mmol lanthanum acetylacetone were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification for 3 h. The reaction temperature was then controlled at 215 °C and the reaction pressure at 2 kPa for prepolymerization for 1 h. When excess ethylene glycol was extracted and the system temperature did not rise, it was confirmed that the ethylene glycol had been extracted. The reaction temperature was then controlled at 215 °C and the reaction pressure at 20 Pa for polycondensation for 3 h. The product discharged was polyglycolic acid copolymerized ethylene sebacic acid glycol ester A3.

[0098] Example 4

[0099] 2 mol of glycolic acid, 1 mol of sebacic acid, 1.3 mol of ethylene glycol, 0.4 mmol of stannous oxalate catalyst, and 0.04 mmol of lanthanum trichloride were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification for 3 h. The reaction temperature was then controlled at 215 °C and the reaction pressure at 2 kPa for prepolymerization for 1 h. When excess ethylene glycol was extracted and the system temperature did not rise, it was confirmed that the ethylene glycol had been extracted. The reaction temperature was then controlled at 215 °C and the reaction pressure at 20 Pa for polycondensation for 3 h. The product discharged was polyglycolic acid copolyethylene sebacic acid ester A4.

[0100] Example 5

[0101] 2 mol of glycolic acid, 1 mol of sebacic acid, 1.3 mol of ethylene glycol, 2 mmol of stannous oxalate catalyst, and 0.2 mmol of lanthanum acetylacetone were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification for 3 h. The reaction temperature was then controlled at 215 °C and the reaction pressure at 2 kPa for prepolymerization for 1 h. When excess ethylene glycol was extracted and the system temperature did not rise, it was confirmed that the ethylene glycol had been extracted. The reaction temperature was then controlled at 215 °C and the reaction pressure at 20 Pa for polycondensation for 3 h. The product discharged was polyglycolic acid copolyethylene sebacic acid ester A5.

[0102] Example 6

[0103] 2 mol of glycolic acid, 1 mol of sebacic acid, 1.3 mol of ethylene glycol, 3 mmol of stannous oxalate catalyst, and 0.03 mmol of lanthanum acetylacetone were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification for 3 h. The reaction temperature was then controlled at 215 °C and the reaction pressure at 2 kPa for prepolymerization for 1 h. When excess ethylene glycol was extracted and the system temperature did not rise, it was confirmed that the ethylene glycol had been extracted. The reaction temperature was then controlled at 215 °C and the reaction pressure at 20 Pa for polycondensation for 3 h. The product discharged was polyglycolic acid copolyethylene sebacic acid ester A6.

[0104] Example 7

[0105] 2 mol of glycolic acid, 1 mol of sebacic acid, 1.3 mol of ethylene glycol, 0.3 mmol of stannous oxalate catalyst, and 0.3 mmol of lanthanum acetylacetone were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification for 3 h. The reaction temperature was then controlled at 215 °C and the reaction pressure at 2 kPa for prepolymerization for 1 h. When excess ethylene glycol was extracted and the system temperature did not rise, it was confirmed that the ethylene glycol had been extracted. The reaction temperature was then controlled at 215 °C and the reaction pressure at 20 Pa for polycondensation for 3 h. The product discharged was polyglycolic acid copolyethylene sebacic acid ester A7.

[0106] Example 8

[0107] 2 mol of glycolic acid, 1 mol of sebacic acid, 1.3 mol of ethylene glycol, 10 mmol of stannous oxalate catalyst, and 10 mmol of lanthanum acetylacetone were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification for 3 h. The reaction temperature was then controlled at 215 °C and the reaction pressure at 2 kPa for prepolymerization for 1 h. When excess ethylene glycol was extracted and the system temperature did not rise, it was confirmed that the ethylene glycol had been extracted. The reaction temperature was then controlled at 215 °C and the reaction pressure at 20 Pa for polycondensation for 3 h. The product discharged was polyglycolic acid copolyethylene sebacic acid ester A8.

[0108] Example 9

[0109] 1.6 mol glycolic acid, 0.8 mol sebacic acid, 1.04 mol ethylene glycol, 0.25 mmol stannous oxalate catalyst, and 0.025 mmol lanthanum acetylacetone were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 160 °C for esterification for 3 h. The reaction temperature was then controlled at 215 °C and the reaction pressure at 2 kPa for prepolymerization for 1 h. When excess ethylene glycol was extracted and the system temperature did not rise, it was confirmed that the ethylene glycol had been extracted. The reaction temperature was then controlled at 215 °C and the reaction pressure at 20 Pa for polycondensation for 3 h. The product discharged was polyglycolic acid copolyethylene sebacic acid ester A9.

[0110] Example 10

[0111] 1.6 mol glycolic acid, 0.8 mol sebacic acid, 1.04 mol ethylene glycol, 0.25 mmol stannous oxalate catalyst, and 0.025 mmol lanthanum acetylacetone were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification for 3 h. The reaction temperature was then controlled at 215 °C and the reaction pressure at 8 kPa for prepolymerization for 1 h. When excess ethylene glycol was extracted and the system temperature did not rise, it was confirmed that the ethylene glycol had been extracted. The reaction temperature was then controlled at 215 °C and the reaction pressure at 20 Pa for polycondensation for 3 h. The product discharged was polyglycolic acid copolymerized ethylene sebacic acid A10.

[0112] Example 11

[0113] 1.6 mol glycolic acid, 0.8 mol sebacic acid, 1.04 mol ethylene glycol, 0.25 mmol stannous oxalate catalyst, and 0.025 mmol lanthanum acetylacetone were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification for 3 h. The reaction temperature was then controlled at 215 °C and the reaction pressure at 2 kPa for prepolymerization for 1 h. When excess ethylene glycol was extracted and the system temperature did not rise, it was confirmed that the ethylene glycol had been extracted. The reaction temperature was then controlled at 215 °C and the reaction pressure at 150 Pa for polycondensation for 3 h. The product discharged was polyglycolic acid copolymerized ethylene sebacic acid glycol ester A11.

[0114] Example 12

[0115] 1.6 mol glycolic acid, 0.8 mol sebacic acid, 1.04 mol ethylene glycol, 0.25 mmol stannous oxalate catalyst, and 0.025 mmol lanthanum acetylacetone were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification for 3 h. The reaction temperature was then controlled at 230 °C and the reaction pressure at 2 kPa for prepolymerization for 1 h. When excess ethylene glycol was extracted and the system temperature did not rise, it was confirmed that the ethylene glycol had been extracted. The reaction temperature was then controlled at 230 °C and the reaction pressure at 20 Pa for polycondensation for 3 h. The product discharged was polyglycolic acid copolyethylene sebacic acid ester A12.

[0116] Example 13

[0117] 1.6 mol of glycolate, 0.8 mol of sebacic acid, 1.04 mol of ethylene glycol, 0.25 mmol of stannous oxalate catalyst, and 0.025 mmol of lanthanum acetylacetone were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification for 3 h. The reaction temperature was then controlled at 215 °C and the reaction pressure at 2 kPa for prepolymerization for 1 h. When excess ethylene glycol was extracted and the system temperature did not rise, it was confirmed that the ethylene glycol had been extracted. The reaction temperature was then controlled at 215 °C and the reaction pressure at 20 Pa for polycondensation for 3 h. The product discharged was polyglycolic acid copolyethylene sebacic acid glycol ester A13.

[0118] Comparative Example 1

[0119] The method was carried out according to Example 1, except that the comonomers sebacic acid and ethylene glycol were not added.

[0120] 1.6 mol of glycolic acid, 0.16 mmol of stannous oxalate catalyst, and 0.016 mmol of lanthanum acetylacetone were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification reaction for 3 h. The reaction temperature was then controlled at 215 °C and the reaction pressure at 2 kPa for prepolymerization reaction for 1 h. Once the top temperature of the fractionation column no longer increased, the reaction pressure was controlled at 20 Pa for polycondensation reaction for 3 h. Polyglycolic acid B1 was then discharged.

[0121] Comparative Example 2

[0122] The method of Example 1 was implemented, except that stannous oxalate was not added.

[0123] 1.6 mol of glycolic acid, 0.8 mol of sebacic acid, 1.04 mol of ethylene glycol, and 0.025 mmol of lanthanum acetylacetonate were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification for 3 h. The reaction temperature was then controlled at 215 °C and the reaction pressure at 2 kPa for prepolymerization for 1 h. After excess ethylene glycol was removed, the reaction pressure was controlled at 20 Pa for polycondensation for 3 h. No polymer was obtained.

[0124] Comparative Example 3

[0125] 1.6 mol glycolic acid, 0.8 mol sebacic acid, 1.04 mol ethylene glycol, and 0.25 mmol stannous oxalate catalyst were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification for 3 h. The reaction temperature was then controlled at 215 °C and the reaction pressure at 2 kPa for prepolymerization for 1 h. After excess ethylene glycol was removed, the reaction pressure was controlled at 20 Pa for polycondensation for 3 h. The product discharged was polyglycolic acid copolyethylene sebacic acid ester B3.

[0126] Comparative Example 4

[0127] 1.6 mol of glycolic acid, 0.8 mol of sebacic acid, 1.04 mol of ethylene glycol, 0.25 mmol of stannous oxalate catalyst, and 0.025 mmol of lanthanum acetylacetone were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification for 3 h. Subsequently, the reaction temperature was maintained at 2 kPa for prepolymerization for 1 h. After excess ethylene glycol was removed, the reaction pressure was controlled at 20 Pa for polycondensation for 3 h. No polymer was obtained.

[0128] Comparative Example 5

[0129] 1.6 mol glycolic acid, 0.8 mol sebacic acid, 1.04 mol ethylene glycol, 0.25 mmol stannous oxalate catalyst, and 0.025 mmol lanthanum acetylacetone were added to a 500 mL three-necked flask. Nitrogen gas was purged for 30 min to remove oxygen. The reactor was then heated to 185 °C for esterification reaction for 3 h. Subsequently, the reaction temperature was controlled at 215 °C and the reaction pressure at 2 kPa for prepolymerization reaction for 4 h, but no polymer was obtained.

[0130] Comparative Example 6

[0131] 135g glycolic acid, 64g sebacic acid, 28g ethylene glycol, and 0.36g stannous oxalate were added to a 500mL three-necked flask. Esterification was carried out for 6 hours under stirring, atmospheric pressure, 190℃, and reflux at 100℃ to obtain the precursor. The obtained precursor was then prepolymerized for 2 hours under stirring, 50kPa reaction pressure, 190℃ reaction temperature, and reflux at 60℃ to obtain the intermediate. 0.14g antioxidant 1010, 0.07g antioxidant 626, and 0.36g stannous oxalate were added to the intermediate. Polycondensation was carried out for 6 hours under stirring, 20Pa reaction pressure, 200℃ reaction temperature, and reflux at 65℃ to obtain the copolymer.

[0132] Performance parameters of Examples 1-13 and Comparative Examples 1-6 were tested, and the results are shown in Table 1.

[0133] Table 1

[0134]

[0135]

[0136] Test case

[0137] Mechanical properties were tested on Examples 1-13 and Comparative Examples 1-6 to obtain test Examples 1-13 and test Comparative Examples 1-6. Performance tests were conducted, and the test results are shown in Table 2.

[0138] Table 2

[0139]

[0140]

[0141] As can be seen from the results in Tables 1 and 2, compared with Examples 1-3, Examples 1 and 3 have different types of second monomers added compared with Example 2. It can be seen that adding different monomers results in different initial properties of the final polymers, and they cannot be compared horizontally. However, compared with Comparative Example 1 (polyglycolic acid homopolymer), Example 2 shows that the polymer prepared in this application has better overall performance.

[0142] Compared with Comparative Examples 3 and 4, no polymer was obtained in Comparative Examples 3 and 4. The technical solution of the present invention can solve the problems of easy oxidation and degradation and difficult processing of polyglycolic acid during preparation.

[0143] Compared with Comparative Examples 1-6, Examples 1-13 demonstrate that the synergistic effect of the compound catalyst and preparation process of the present invention enables the polyglycolic acid copolymer prepared according to the technical solution of the present invention to have a higher molecular weight and polymer content, thereby possessing higher thermal stability, higher viscosity, and higher toughness.

[0144] Furthermore, compared to Examples 5-8, the synergistic effect of the specific molar ratio of the first catalyst to the total molar ratio of the first monomer and the second monomer, and the molar ratio of the second catalyst to the total molar ratio of the first monomer and the second monomer, enhances the viscosity of the polymer, increases the molecular weight and degree of polymerization of the polymer, and reduces the content of polymer end groups.

[0145] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A method for preparing a polyglycolic acid copolymer, characterized in that, Includes the following steps: (1) At a first temperature, the first monomer, the second monomer and the third monomer are subjected to an esterification reaction under the action of the first catalyst and the second catalyst to obtain the precursor; (2) The precursor is heated to a second temperature and a first pressure to undergo a prepolymerization reaction to obtain an intermediate; the pressure is reduced to a second pressure to undergo a polycondensation reaction to obtain a copolymer; The first monomer is selected from glycolic acid and / or glycolate; The second monomer is selected from diacids and / or diacid anhydrides; The third monomer is a diol; The first catalyst is an organometal salt, wherein the metal element in the organometal salt is selected from titanium and / or tin, and the metal-bonded portion in the organometal salt is selected from at least one of α-alkoxy, α-alkyl monocarboxylic acid, and α,ω-alkyl diacid. The second catalyst is a RE(R1)3 type catalyst, where RE is a rare earth metal element and R1 is selected from acetylacetone group; The molar ratio of the first catalyst to the total molar ratio of the first monomer and the second monomer is 1:(3.33×10⁻⁶). 2 -10 5 The molar ratio of the second catalyst to the total molar ratio of the first monomer and the second monomer is 1:(3.33×10⁻⁶). 2 -10 5 .

2. The method according to claim 1, wherein, The rare earth metal element is selected from at least one of yttrium, lanthanum, cerium, praseodymium, neodymium, terbium, ytterbium, dysprosium, samarium, and scandium.

3. The method according to claim 2, wherein, The rare earth metal element is selected from at least one of lanthanum, cerium, and neodymium.

4. The method according to claim 1, wherein, The second catalyst is lanthanum acetylacetone.

5. The method according to claim 1, wherein, The molar ratio of the first monomer to the second monomer is 0.1-9:1; And / or, the molar ratio of the third monomer to the second monomer is 1.1-2:

1.

6. The method according to claim 5, wherein, The molar ratio of the first monomer to the second monomer is 0.2-4:1; And / or, the molar ratio of the third monomer to the second monomer is 1.15-1.5:

1.

7. The method according to claim 6, wherein, The molar ratio of the first monomer to the second monomer is 0.8-2:1; And / or, the molar ratio of the third monomer to the second monomer is 1.2-1.3:

1.

8. The method according to claim 1, wherein, The molar ratio of the first catalyst to the total molar ratio of the first monomer and the second monomer is 1:(5×10⁻⁶). 2 )-(2×10 4 ); And / or, the molar ratio of the second catalyst to the total molar ratio of the first monomer and the second monomer is 1:(2×10⁻⁶). 3 -10 5 .

9. The method according to claim 8, wherein, The molar ratio of the first catalyst to the total molar ratio of the first monomer and the second monomer is 1:(2×10⁻⁶). 3 -10 4 ; And / or, the molar ratio of the second catalyst to the total molar ratio of the first monomer and the second monomer is 1:(2×10⁻⁶). 4 -10 5 .

10. The method according to claim 1, wherein, The metal element in the organometallic salt is tin.

11. The method according to claim 1, wherein, The first catalyst is selected from at least one of tetraisopropyl titanate, tetrabutyl titanate, tin laurate, stannous octoate, and stannous oxalate.

12. The method according to claim 11, wherein, The first catalyst is selected from stannous octoate and / or stannous oxalate.

13. The method according to claim 12, wherein, The first catalyst is stannous oxalate.

14. The method according to claim 1, wherein, The dicarboxylic acid is selected from at least one of 2,5-furandicarboxylic acid, terephthalic acid, phthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 1,4-succinic acid, 1,5-glutaric acid, 1,6-adipic acid, 1,8-octanoic acid, 1,10-sebacic acid, and 1,4-cyclohexanedicarboxylic acid. And / or, the dicarboxylic anhydride is selected from malondiic anhydride, succinic anhydride, glutaric anhydride, adipic anhydride, octanoic anhydride, sebacic anhydride and phthalic anhydride; And / or, the diol is selected from at least one of ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,2-propanediol, 2-methyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, 1,3-butanediol, neopentanediol, 1,4-cyclohexanediol, 1,6-cyclohexanediol, diethylene glycol, triethylene glycol, polyethylene glycol, p-phenol, diethyl terephthalate, dihydroxypropyl terephthalate, dihydroxybutyl terephthalate, dihydroxyhexyl terephthalate, tetrahydrofuran 3,4-diol, isosorbide, iso-idyl alcohol, and isomannitol.

15. The method according to claim 14, wherein, The dicarboxylic acid is selected from at least one of 2,5-furandicarboxylic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, 1,4-succinic acid, 1,6-adipic acid, 1,10-sebacic acid and 1,4-cyclohexanedicarboxylic acid; And / or, the dicarboxylic anhydride is sebacic anhydride; And / or, the diol is selected from at least one of ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,2-propanediol, 2-methyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, diethyl terephthalate, dipropyl terephthalate, dibutyl terephthalate, dihexyl terephthalate, tetrahydrofuran 3,4-diol, and isosorbide.

16. The method according to claim 15, wherein, The dicarboxylic acid is selected from at least one of 2,5-furandicarboxylic acid, terephthalic acid, and 1,10-sebacic acid; And / or, the diol is selected from at least one of ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, diethyl terephthalate, dibutyl terephthalate, dihexyl terephthalate, and isosorbide.

17. The method according to claim 16, wherein, The dicarboxylic acid is selected from terephthalic acid and / or 1,10-sebacic acid; And / or, the diol is selected from 1,4-butanediol and / or bis(hydroxybutyl) terephthalate.

18. The method according to claim 1, wherein, Step (1) also includes: performing deoxygenation before the reaction to ensure that both the first esterification reaction and the second esterification reaction are carried out in an inert gas atmosphere.

19. The method according to claim 18, wherein, The deoxygenation time is 10-100 min.

20. The method according to claim 19, wherein, The deoxygenation time is 10-30 minutes.

21. The method according to claim 1, wherein, The first temperature is 100-190℃; And / or, the esterification reaction takes 1-6 hours.

22. The method according to claim 21, wherein, The first temperature is 175-185℃; And / or, the esterification reaction takes 2-4 hours.

23. The method according to claim 1, wherein, The second temperature is 190-235℃; And / or, the first pressure is 0.1-100 kPa; And / or, the prepolymerization reaction takes 0.5-2 hours; And / or, the second pressure is ≤200Pa; And / or, the temperature of the polycondensation reaction is 190-235°C; And / or, the polycondensation reaction takes 1-6 hours.

24. The method according to claim 23, wherein, The second temperature is 200-225℃; And / or, the first pressure is 0.1-2 kPa; And / or, the prepolymerization reaction takes 1-2 hours; And / or, the second pressure is 20-200 Pa; And / or, the temperature of the polycondensation reaction is 200-225°C; And / or, the polycondensation reaction takes 2-4 hours.

25. A polyglycolic acid copolymer prepared by the method according to any one of claims 1-24.

26. The polyglycolic acid copolymer according to claim 25, wherein, The polyglycolic acid copolymer has a thermal decomposition temperature ≥300℃ and an intrinsic viscosity ≥1dL / g at 25℃.

Citation Information

Patent Citations

  • Degradable copolyester composition, anti-static biodegradable film material, film and application

    CN115637026A

  • High-molecular-weight aliphatic copolyester and its production

    JP1996311181A

  • Biodegradable high molecular weight aliphatic polyesterether and its production

    JP1999166044A

  • Process for making poly(glycolic acid) for containers and films with reduced gas permeability

    US20210198424A1